A comprehensive prognostic and immunological analysis of hexokinase domain containing protein-1 (HKDC1) in pan-cancer - Zhi Liang; Tianhao Zhang; Jiajia Huang; Zhixin Huang; Zeyu Zhao; Shirong Cai; Jinping Ma (PeerJ)
Background Currently, research on the role of hexokinase domain-containing protein-1 (HKDC1) in neoplasm metabolism remains sparse. This study seeks to conduct a thorough investigation of HKDC1’s potential functions across thirty-three different tumor types, utilizing data obtained from The Cancer Genome Atlas (TCGA). Method We conducted a thorough data extraction from the TCGA database, subsequently employing R (version 4.2.2) and its associated software packages for detailed analysis. Our investigation centered on evaluating the differential expression and prognostic significance of HKDC1, while also examining its connections to tumor heterogeneity, mutation profiles, and RNA modifications. Furthermore, we analyzed the relationship between HKDC1 expression and tumor immunity utilizing the TIMER analysis approach. Results A comprehensive analysis of various tumor types has revealed that HKDC1 is significantly upregulated in many malignant tumors. Importantly, patients with elevated HKDC1 levels in their tumor tissues often experience poorer prognoses. The association between HKDC1 expression, immune cell infiltration, and the existence of immune checkpoints suggests a possible connection between the tumor microenvironment and HKDC1, alongside tumor advancement. Gene set enrichment analysis (GSEA) further substantiates the idea that HKDC1 may play a role in several critical pathways and biological processes associated with neoplasm. Additionally, the overexpression of HKDC1 is influenced by promoter methylation and alterations in DNA copy number amplification. Furthermore, in vitro experiments demonstrated that silencing HKDC1 resulted in a marked reduction in the proliferation, migration, and invasion capabilities of neoplasm cells. Conclusion Our initial pan-cancer analysis provided a comprehensive understanding of the oncogenic roles of HKDC1 across diverse cancer types. Moreover, HKDC1 has the potential to serve as a significant prognostic biomarker.